JAEPL, Vol. 8, Winter 2002-2003 - Katie S. Fleckenstein; Linda T. Calendrillo (Journal of the Assembly for Expanded Perspectives on Learning, 2002)
Essays Charles Suhor. James Moffett's Lit Crit and Holy Writ. In one of Moffett's final presentations, he traced parallels between literary criticism and the study of scripture from various traditions. He explained the development of his Points of View spectrum as a response to his high school teaching experiences and presented an updated version of the spectrum. Gina Briefs-Elgin. Something to Have at Heart: Another Look at Memorization. After tracing the history of learning by heart, this essay explores its advantages and suggest that we restore this time-honored practice which can enrich our students' relationships with words and books and empower their personal lives. Christopher C. Weaver. The Rhetoric of Recovery: Can Twelve Step Programs Inform the Teaching of Writing? The article examines the spiritual dimensions of recovery programs and explores some of the ways the rhetoric of these programs as well as the structure of twelve step meetings may illuminate the nature of composition classes and particularly of peer writing groups. Brenda Daly. Stories of Re-Reading: Inviting Students to Reflect to Their Emotional Responses to Fiction. Although most literature courses teach students to focus on textual analysis, this essay argues that students should be given opportunities for exploring their emotional responses to the text. Devan Cook. Successful Blunders: Reflection, Deflection, Teaching. Often we expect students' experience with assignments to reflect our own or those of previous students, but we may blunder when we base our teaching on past successes. By deflecting such assignments and constructing unexpected identities, students and instructors alike learn and teach. Terrance Riley. The Accidental Curriculum. True learning—learning which results in some permanent cognitive change—is far too unpredictable to be controlled by format curricular designs. The formal curriculum of English studies is valuable largely as a stage setting for educational accidents. Robbie Clifton Pinter. The Landscape Listens—Hearing the Voice of the Soul. This essay offers a view of Mary Rose O'Reilley's "radical listening," applying it to the classroom as a way for teachers and students to "learn to their lives." Helen Walker. Connecting. Lisa Ruddick—We Are the Poetry Kathleen McColley Foster—Becoming a Professional: A Coming of Age Narrative from the 4C's Chauna Craig—Writing the Bully Steven VanderStaay—Discipline 101 Meg Peterson—To Live Wildly Linda K. Parkyn—Coming Full Circle Reviews Nathaniel Teich. Reading, Writing, and Rising Up: Teaching About Social Justice and the Power of the Written Word. (Linda Christensen, 2000). Hepzibah Roskelly. Everyone Can Write: Essays Toward a Hopeful Theory of Writing and Teaching Writing. (Peter Elbow, 2000). Emily Nye. Saying and Silence: Listening to Composition with Bakhtin. (Frank Farmer, 2001). Dennis Young. Teaching With Your Mouth Shut. (Donald L. Finkel, 2000).